(untitled) (Marketing Journal, 2026)
The article examines the economic aspects of improving investment process management in the green economy. Key sustainable finance instruments such as green bonds, ESG investments, and climate funds were analyzed. A conceptual model was proposed, integrati ng institutional mechanisms and financial incentives. Global trends № 1 -SON YANVA R, 202 6-YIL 300 in energy transition investments and barriers to green capital access in developing countries were addressed. Empirical data confirmed a positive correlation between ESG performance and financial outcomes. Practical recommendations were developed to scale up green finance under constrained public budgets. The findings can be applied in formulating national strategies for sustainable investment development.